Strategi Ekspansi Global Pada Perusahaan Starbucks Dalam Bisnis Internasional - Afriani Manullang; Dinda Cinta Nainggolan; Karin Aurani; Nichollin Stiffanny; Sherina Alim; Hafiza Adlina (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
Expansion is an effort to expand or enlarge the business network of a company. It can have positive impacts, such as expanding sales, but also has risks. Starbucks is an example of a company that has expanded globally. By the beginning of the 21st century, Starbucks was present in dozens of countries and operated more than 20,000 stores.Systematic review of primary studies to find relevant studies on global expansion of international trade.Starbucks has successfully grown worldwide with strong goals and ambitions to expand, according to previous research.Starbucks used market study and monitoring to increase profits, revenue, sales, and locations. Companies must adapt to local demands, minimize costs, strengthen brands, and conduct an international business risk analysis.